Utility of Peripheral Blood Smear in Thrombocytopenic Patients for Platelet Count Estimation - KG, Dr.Varaprasad; Kavyasree, Dr.B.; Dussa, Dr.Tejaswi; S, Dr.Jhansi; Harikumar, Dr.S.R; Ramamurthy, Dr.B. (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: In most of the laboratories, the Hematology analyzer is utilized to count platelets in patient blood samples. Although Hematology analyzers normally produce an accurate platelet count, their accuracy has been brought into question while enumerating low platelet counts, platelet abnormalities, or platelet-like fragment interference[6]. Peripheral blood film is highly useful in the diagnosis of unexplained thrombocytopenia i.e pseudo-thrombocytopenia and also in monitoring the therapeutic response. Materials & Methods: Platelet count in analyser and peripheral smear examined for the patients with low platelet count in analyser. The statistical analysis was done by using pearson correlation coefficient. Results: We studied 15 patients with thrombocytopenia i.e. < 150 x 103/uL platelet count on automated cell counter. We observed. The mean platelet count on automated analyzers was 0.67+ 0.24 lakhs/cu.mm whereas the mean platelet count verified on peripheral smear was 1.09+ 0.45lakhs/cu.mm with a significant difference between the two groups. Conclusion: platelet count estimation by PBS method is reliable and statistically significant when compared to haematology analyser especially in pseudo thrombocytopenia cases.